Analisis Kesesuaian Lahan Permukiman di Kecamatan Gandus Kota Palembang - Hera Angelita Trisna Amelia; Hala Haidir; Hendry Natanael Gumano (Jurnal Ilmiah Wahana Pendidikan, 2022)
The city of Palembang experienced an increase in activity and population growth of 5% per year, causing many areas in the middle of the city to experience saturation, encouraging the development of Gandus sub-district as a new residential area. Settlements must be built on the land according to their designation. So the purpose of this research is to analyze and determine the suitability of land and priority areas for development as residential land. The descriptive quantitative method was used in this study, with a spatial analysis approach and ArcGIS 10.8 as the analysis tool. Overlay analysis with tools union and intersect, scoring, buffering, cross, and elimination are the analytical techniques employed. The results of this research are that the Gandus sub-district is divided into two area functions, namely the function of the 4754 ha cultural area and the function of the 35 ha nutrient area. Then the suitable land to be developed into residential land by eliminating the limiting factors and land use that is not suitable for settlements obtained unsuitable land is 2455 Ha and suitable land for settlement is 2351 Ha, the land is defined as priority area with priority area I 21.37 ha, priority area II 1355.27 ha and priority area III 986.24 ha.